The legacy of Friedrich List: The expansive reproduction system and the Korean history of industrialization - Bogang Jun; Alexander Gerybadze; Tai-Yoo Kim (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
This study revisits the theory of Friedrich List from a more comprehensive and modernized perspective and applies it to the Korean history of industrialization. Although List is well known as the scholar who insisted on the protection of infant industry, his argument on protectionism is a part of the broader picture depicted in his book The National System of Political Economy (1841). This study follows his theoretical legacy in various fields of study. Although we can find his theoretical influence in several fields of research such as the national innovation system, concept of national competitiveness, and theory of developmental state, these studies fail to embrace all the arguments of List. Additionally, theses models focus more heavily on the explanation of historical and regional development phenomena without providing general principles of economic development behind the phenomena. This study therefore aims to suggest the expansive reproduction system as a generalized and modernized version of List's theory and to show its example by using the Korean history of industrialization. Consequently, we argue that the economic development of Korea has been achieved by putting the theory of List into practice.
urn:nbn:de:bsz:100-opus-11894
Keywords: 330; Friedrich List; Economic Development; Korean Economic History; Economic Policy